Predictors of multidrug-resistant Pseudomonas aeruginosa in neutropenic patients with bloodstream infection. (March 2020) - Viasus, D.; Puerta-Alcalde, P.; Cardozo, C.; Suárez-Lledó, M.; Rodríguez-Núñez, O.; Morata, L.; Fehér, C.; Marco, F.; Chumbita, M.; Moreno-García, E.; Fernández-Avilés, F.; Gutiérrez-Garcia, G.; et al.
Abstract: Objectives: To assess risk factors for multidrug-resistant Pseudomonas aeruginosa (MDR-PA) infection in neutropenic patients. Methods: Single-centre retrospective analysis of consecutive bloodstream infection (BSI) episodes (2004–2017, Barcelona). Two multivariate regression models were used at BSI diagnosis and P. aeruginosa detection. Significant predictors were used to establish rules for stratifying patients according to MDR-PA BSI risk. Results: Of 661 Gram-negative BSI episodes, 190 (28.7%) were caused by P. aeruginosa (70 MDR-PA). Independent factors associated with MDR-PA among Gram-negative organisms were haematological malignancy (OR 3.30; 95% CI 1.15–9.50), pulmonary source of infection (OR 7.85; 95% CI 3.32–18.56), nosocomial-acquired BSI (OR 3.52; 95% CI 1.74–7.09), previous antipseudomonal cephalosporin (OR 13.66; 95% CI 6.64–28.10) and piperacillin/tazobactam (OR 2.42; 95% CI 1.04–5.63), and BSI occurring during ceftriaxone (OR 4.27; 95% CI 1.15–15.83). Once P. aeruginosa was identified as the BSI aetiological pathogen, nosocomial acquisition (OR 7.13; 95% CI 2.87–17.67), haematological malignancy (OR 3.44; 95% CI 1.07–10.98), previous antipseudomonal cephalosporin (OR 3.82; 95% CI 1.42–10.22) and quinolones (OR 3.97; 95% CI 1.37–11.48), corticosteroids (OR 2.92; 95% CI 1.15–7.40), and BSI occurring during quinolone (OR 4.88; 95% CI 1.58–15.05) and β-lactam other than ertapenem (OR 4.51; 95% CI 1.45–14.04) were independently associated with MDR-PA. Per regression coefficients, 1 point was assigned to each parameter, except for nosocomial-acquired BSI (3 points). In the second analysis, a score >3 points identified 60 (86.3%) out of 70 individuals with MDR-PA BSI and discarded 100 (84.2%) out of 120 with non-MDR-PA BSI. Conclusions: A simple score based on demographic and clinical factors allows stratification of individuals with bacteraemia according to their risk of MDR-PA BSI, and may help facilitate the use of rapid MDR-detection tools and improve early antibiotic appropriateness.